The drainage exchange of stormwater potential in flat area problems - Musa, Sabariah (David Publishing, 2010)
Groundwater as an alternative source still does not contribute to the water supply in the area of Parit Raja because of the limitation of the water availability in the ground. This lacking of groundwater could be caused by the circumstance that the top layer of the soil is dominated by compacted clay around 2 meters in which its permeability is small, so the water is difficult to infiltrate to the ground. The recharge well technique was designed based on the flat area problems, layer of real condition, flow water table and low infiltration rate. Resistivity soundings were made at existing wells to assess the subsurface layers. Besides that, the past records on floods event, sub surface and surface studies were collected around the study area as a preliminary study. It was presented that the study area promised good prospects to increase the capability of the groundwater and contribute to the drainage system by reducing the volume of rainfall runoff using the recharge well technique.